Service Quality and Its Impact on Customer Satisfaction in Shopping Malls - Vetrivel, S. C. (Journal of Commerce and Trade, 2015)
Retail industry plays a significant role in increasing productivity across a wide range of consumer goods and services, and it is a big business in developed countries, and it is in a much more organized format in India. Most of the retailing in India happens in the un-organized sector with over 12 million retail outlets of various sizes and formats. Retailing involves direct interface with the customer and co-ordination of business activities from end-to-end right from the concept or design stage of the product and delivery of service to the customers. Changing customer’s lifestyle and the competitive environment has made the customers’ expectations grow high. The retailers were more concise with satisfying their customers since the customer satisfaction will be the core point of improving the retailer’s products and services. So the researcher has made an attempt to measure the satisfaction level of customers in the shopping mall.